2018
DOI: 10.1002/jcb.28059
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐suppressive microRNA‐10a inhibits cell proliferation and metastasis by targeting Tiam1 in esophageal squamous cell carcinoma

Abstract: Aberrant microRNAs (miRNAs) expressions could contribute to the progression of numerous cancers, including esophageal squamous cell carcinoma, while miR‐10a participates in multiple biological processes on cancers. However, the molecular mechanism of miR‐10a in esophageal squamous cell carcinoma (ESCC) has not been investigated. Herein, miR‐10a was significantly reduced in ESCC clinical tissues and ESCC cell lines (EC109 and TE‐3). In addition, immunohistochemistry indicated that the expressions of α‐SMA, Ki‐6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Third, several studies also suggested that Tiam1 overexpression could promote the in vitro proliferation of malignant cells and in vivo growth of tumor. [24][25][26][27] As above, it can be easily deduced that Tiam1 expression in cancer cells is required for facilitating tumor growth, invasion, metastasis and chemo-resistance, which supports the prognostic value of Tiam1. Therefore, Tiam1 in tumor cells may be an attractive therapeutic target.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Third, several studies also suggested that Tiam1 overexpression could promote the in vitro proliferation of malignant cells and in vivo growth of tumor. [24][25][26][27] As above, it can be easily deduced that Tiam1 expression in cancer cells is required for facilitating tumor growth, invasion, metastasis and chemo-resistance, which supports the prognostic value of Tiam1. Therefore, Tiam1 in tumor cells may be an attractive therapeutic target.…”
Section: Discussionmentioning
confidence: 56%
“…T-cell lymphoma invasion and metastasis-inducing factor 1 (Tiam1), a specific guanine nucleotide exchange factor, a member of the Rho GTPase family, was first discovered by Habets et al and identified as an invasion and metastasisrelated gene in mice with aggressive T-cell lymphoma. 4,5 The TIAM1 gene is located in the q22 band of chromosome 21 and the centromeric end of the AML 21 gene and contains 2 exons (~7.3 kb) separated by 1 intron (14 kb) 6 Tiam1 is mainly expressed in normal brain and testis tissues with only minimal or no expressions detected in other normal tissues 7 Additionally, Tiam1 is highly expressed in various cancers as well, 6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and its overexpression in cancer cells could contribute to proliferation, [24][25][26][27] invasion and metastasis, [28][29][30][31] angiogenesis 32 and chemo-resistance of cancer cells 33 Of note, Tiam1 expressed in tumor stromal microenvironment also plays a role in regulating tumor invasion, metastasis and chemo-resistance. Cancer-associated fibroblast (CAF) is a major stromal cell in cancer stromal microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major regulatory mechanisms of miRNAs is the inhibition of gene expression through binding to the 3′UTR of target mRNAs . A number of studies have reported that miRNAs exerted antitumor functions in cancers in such manner, including in ESCC . MiR‐488‐3p has also been reported to inhibit tumor progression by targeting oncogene in glioma and melanoma .…”
Section: Discussionmentioning
confidence: 99%
“…8,9,14 A number of studies have reported that miRNAs exerted antitumor functions in cancers in such manner, 10,35 including in ESCC. 4,36 MiR-488-3p has also been reported to inhibit tumor progression by targeting oncogene in glioma and melanoma. 15,30 In our study, we predicted through TargetScan the potential targets for miR-488-3p, among which we chose ZBTB2 for further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Many such studies have been published so far, which reveal miRNAs as tumor suppressors or oncogenes (Table 1). For example, miR-146a, miR-133b, miR-106b-3p, miR-219-5p, miR-206, miR-384, miR-455-5p, miR-128, miR-145-3p/5p, miR-10b-3p, miR-874-3p, miR-10a, miR-365, miR-301a, miR-6775-3p, miR-139-5p, miR-516b, miR-449a-5p, miR-125b, miR-433-3p, miR-370, miR-133b, miR-30a-3p/5p, miR-34a, miR-196a, and miR-125b-5p have been shown to act as tumor suppressors by inhibiting ESCC cell proliferation, promoting apoptosis by directly targeting oncogenes, or antagonizing pro-cancer signaling pathways [29,33,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][60][61][62][63]110,133]. In contrast, pro-oncogenes such as miR-141, miR-21, miR-10b-3p, miR-424, miR-675-3p, miR-543, miR-135, miR-23b-3p, miR-502, miR-21-5p, and miR-548k have been reported to play contrasting roles in promoting cell proliferation or suppressing apoptosis in ESCC [47,[64][65][66][67][68][69][70][71][72][73].…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%